A fractionation of acid-soluble non-exchangeable potassium in some New Zealand soils into available and non-available forms : a thesis presented for the degree of Doctor of Philosophy, University of New Zealand [Massey Agricultural College] - Haylock, Owen Fillbridge (Massey University, 1956)
One of the most ubiquitous of the mineral elements present in plants, potassium plays on important and essential rôle in their nutrition, being required in large amounts for healthy plant growth. Unlike nitrogen, phosphorus, calcium and magnesium, potassium does not enter into premanent organic combinations in plants but appears to exist in solution as potassium ions in conjunction with soluble inorganic and organic anions. Consequently, specific rôles in the growth of plants are difficult to assign to potassium and only by inference from comparisons of normal and potassium deficient plants can functions he attributed to potassium. The following summary of the effects of potassium on the physiology of plants, abstracted from the review made by Lawton & Cock (1955), shows that potassium affects the following processes.
Keywords: Soils; Potassium content; New Zealand; Acid-soluble non-exchangeable potassium